(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objectives: The aim of the study was to assess the attitude of the undergraduate medical students towards the assessment system of revised medical curriculum. Materials and Methods: Study design: It was a -descriptive cross sectional study. Study period: From February 2008 to April 2008. Setting: Department of Obstetrics and Gynaecology in Holy Family Red Crescent Medical College and Hospital. Sample size: Total 82 students were selected for the study out of which 70 participated. Inclusion criteria: students who were selected for the final MBBS examination. Exclusion Criteria: Students not qualified for final professional examination. Procedure: During the placement of the students in the department of Obstetrics and Gynaecology, the basic idea of the old and the new curriculum was explained to them. The objective of the study was explained and a pretested questionnaire was given to each student. Identification of the student was not compulsory to maintain secrecy. 5 point Likert scales was used to measure the responses of the participants. Statistical analysis was done using the SPSS system version 11. Results: Out of 82 students, 70 participated. Among them, 37.1% were male, and 48.6% were female students. 44.2 % said that the curriculum and 35.7 % said that the exam system is easy to follow, 47.1 % wanted to have single subject and 65.7% wanted to have all the major subjects simultaneously in block posting. 74.1 % said that the 6 hours learning period is tiring. 42.9 % were in favour of 3-6 pm break, 64.3% were in favour of giving MOCK test weekly, 55.7 % liked formative assessment test, 64.3 % did not adopt any unfair means in the examination, 78.6% students are comfortable with MCQ,81.4 % with SAQ, about 41.5% with SEQ, 74.2% with OSPE, 71.5% with SOE and 77.2% liked Clinical examination. Key Words: Under graduate medical Curriculum; Students opinion. DOI: 10.3329/jbcps.v28i3.6508 J Bangladesh Coll Phys Surg 2010; 28: 151-156